2023
DOI: 10.1002/adom.202302682
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorescence by Trapping Defects in Boric Acid Induced by Thermal Processing

Luigi Stagi,
Luca Malfatti,
Alessia Zollo
et al.

Abstract: The phosphorescence of boric acid (BA, H3BO3) at room temperature is a puzzling phenomenon subject to controversial interpretations although the role of structural defects has not yet been considered. Heat treatments of boric acid cause its transformation into the metaboric phase and amorphous boron oxide (B2O3). The structural changes after thermal processing can create defects that become centers of luminescence and recombination channels in the visible range. In the present work, commercial boric acid is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Furthermore, when the concentration of CDs decreases to 1% or lower, the visible afterglow time reaches a maximum value of around 10 s. As the concentration of CDs decreases to a lower level, the luminescent intensity decreases, and the afterglow time remains the same. Although there are some reports indicating that BA may also exhibit phosphorescence, , and phosphorescence from BA itself is weak and hardly observed in this research (Figure S6: pictures of BA under and after UV), the extensive lifespan and color regulation space in this work should be attributed to CDs. This time difference provides new anticounterfeiting ideas.…”
Section: Resultsmentioning
confidence: 59%
“…Furthermore, when the concentration of CDs decreases to 1% or lower, the visible afterglow time reaches a maximum value of around 10 s. As the concentration of CDs decreases to a lower level, the luminescent intensity decreases, and the afterglow time remains the same. Although there are some reports indicating that BA may also exhibit phosphorescence, , and phosphorescence from BA itself is weak and hardly observed in this research (Figure S6: pictures of BA under and after UV), the extensive lifespan and color regulation space in this work should be attributed to CDs. This time difference provides new anticounterfeiting ideas.…”
Section: Resultsmentioning
confidence: 59%
“…Several research groups have observed the rise of such fluorescence, which is explained by the possible presence of defects. Based on experiments performed on boron nitride nanostructures, it was hypothesized that this effect may also be directly related to the formation of structural defects in boron oxide . The investigation of boron oxide phase transitions during heat treatments at increasing temperatures revealed the occurrence of structural modifications when H 3 BO 3 melts and afterward recrystallizes (Figure ).…”
Section: From Bn Defects To Boron Oxide Structural Defects At Origin ...mentioning
confidence: 99%
“…Gray and light blue areas highlight the temperature interval between the two H 3 BO 3 dehydration processes. Reproduced from ref . Copyright 2023 Wiley.…”
Section: From Bn Defects To Boron Oxide Structural Defects At Origin ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ultralong room-temperature phosphorescence (RTP) has important applications in the fields of optoelectronics, light-emitting diodes, biological imaging, anticounterfeiting technology, etc. Conventional RTP phosphors usually rely on inorganic compounds containing rare earth/transition metals, which have strong spin–orbit coupling for the intersystem crossing between singlet and triplet excitons. , Pure organic phosphors with long-lived RTP have attracted increasing interest recently as a result of their advantages of low cost, easy fabrication, non-toxicity, and high biological compatibility. ,, Especially, some pure single-component molecular crystals were also reported to be able to emit RTP, e.g., the crystals of carbazole derivatives, triazine derivatives, and boric acid (BA). The origin of RTP in these single-component molecular crystals has aroused heated debate in the community. RTP of them is originally attributed to H aggregation in the molecular packing for the carbazole derivatives and triazine derivatives and to weak conjugation between the n electrons of O atoms for BA by their finders. Chen et al and Wu et al later argue that impurities in the commercial molecular crystal sources should be responsible for RTP in the carbazole derivatives and BA; i.e., the crystals used in previous experiments are not pure actually. , Ding et al further report that even trace impurity (<0.1%) can achieve bright RTP in molecular crystals .…”
mentioning
confidence: 99%